"More Confident Going into College": Lessons Learned from Multiple Stakeholders in a New Blended Learning Initiative - Whiteside, Aimee L.; Garrett Dikkers, Amy; Lewis, Somer (Online Learning, 2016)
This article examined a blended learning initiative in a large suburban high school in the Midwestern region of the United States. It employed a single-case exploratory design approach to learn about the experience of administrators, teachers, students, and parents. Using Zimmerman’s Self-Regulated Learning (SRL) Theory as a guiding framework, this study explored surveys, face-to-face observation data, interview transcriptions, and focus group transcriptions to learn about different stakeholders’ experiences and their observations about student readiness for blended learning. As a result, the data suggested three major themes, namely how blended learning initiatives can promote autonomy and self-regulation, encourage inquiry and build relationships, and ultimately help students feel ready for college.